2022
DOI: 10.1186/s12889-022-13638-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID- 19 and human right to food: lived experiences of the urban poor in Kenya with the impacts of government’s response measures, a participatory qualitative study

Abstract: Background Globally, governments put in place measures to curb the spread of COVID-19. Information on the effects of these measures on the urban poor is limited. This study aimed to explore the lived experiences of the urban poor in Kenya in the context of government’s COVID-19 response measures and its impact on the human right to food. Methods A qualitative study was conducted in two informal settlements in Nairobi between January and March 2021.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Countries across the globe have applied social distancing measures together with vaccination in an attempt to slow the spread of the virus. These social distance measures and restrictions aimed at mitigating the pandemic have been shown to worsen vulnerabilities such as anxiety, loss of livelihoods, uncertainty and violation of human rights, as demonstrated in earlier studies ( Kansiime et al, 2021 ; Kimani-Murage et al, 2022 ; Rahman et al, 2021 ). In the short term, the socio-economic impacts of the COVID-19 pandemic have disrupted work arrangements and livelihood activities.…”
Section: Introductionmentioning
confidence: 69%
“…Countries across the globe have applied social distancing measures together with vaccination in an attempt to slow the spread of the virus. These social distance measures and restrictions aimed at mitigating the pandemic have been shown to worsen vulnerabilities such as anxiety, loss of livelihoods, uncertainty and violation of human rights, as demonstrated in earlier studies ( Kansiime et al, 2021 ; Kimani-Murage et al, 2022 ; Rahman et al, 2021 ). In the short term, the socio-economic impacts of the COVID-19 pandemic have disrupted work arrangements and livelihood activities.…”
Section: Introductionmentioning
confidence: 69%
“…For example, health service disruption has been documented through time-series analyses in Kenya which showed that the biggest declines in activity were in outpatient visits and childhood immunisations, with some rebound as the pandemic evolved(23). Several studies have documented the radical economic shocks precipitated by the pandemic, including globally/regionally(24) and within Kenyan slums particularly, where the pandemic and resulting government policies were reported to have had devastating consequences on the livelihood of slum dwellers who were “left to choose between life and livelihood”(25), “violating” their human right to food(26). Such findings were replicated in Bangladesh, where the impacts on household economics (27,28) and the mental health of caregivers (27) were stark.…”
Section: Discussionmentioning
confidence: 99%
“…As with previous crises, urban agriculture during the Covid-19 pandemic has been positioned as a solution to address the negative impact of the crisis on the food sector (Nchanji & Lutomia, 2021;Paganini et al, 2020;Sridhar et al, 2022). The pandemic and associated restrictions disrupted the food supply chain (Khan et al, 2020) and created food insecurity (Houessou et al, 2021;Kimani-Murage et al, 2022) by interrupting the regular flow of food from producers to consumers, leading to increased food prices, labor supply issues, and reduced access to and availability of food (Bulgari et al, 2021;Kimani-Murage et al, 2022;Priyadarshini & Abhilash, 2021). At the same time, the lockdowns reduced income due to restrictions on movement and the decline in business (Manda, 2022), creating economic barriers to access food.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the study of Mead et al (2022), which indicated that home food growing in the United Kingdom during Covid-19 resulted in a lower level of food insecurity and a higher level of well-being. Due to the multifunctionality of urban agriculture, it was promoted in various cities during Covid-19 (Janowska et al, 2022;Music et al, 2022;Kimani-Murage et al, 2022).…”
Section: Introductionmentioning
confidence: 99%